Iminodiacetic acid functionalized magnetic nanoparticles for speciation of Cr(iii) and Cr(vi) followed by graphite furnace atomic absorption spectrometry detection. Issue 14 (26th January 2017) - Wei, Wenye; Zhao, Bingshan; He, Man; Chen, Beibei; Hu, Bin
Abstract : In this work, iminodiacetic acid (IDA) functionalized magnetic nanoparticles (Fe3 O4 @SiO2 @IDA) were prepared and the adsorption behavior of Cr(iii )/(vi ) on them was investigated. Abstract : In this work, iminodiacetic acid (IDA) functionalized magnetic nanoparticles (Fe3 O4 @SiO2 @IDA) were prepared and the adsorption behavior of Cr(iii )/(vi ) on them was investigated. It was found that both Cr(iii ) and Cr(vi ) could be quantitatively retained on Fe3 O4 @SiO2 @IDA in the pH range of 2.5–3.5, while only Cr(iii ) could be adsorbed in the pH range of 4.0–9.0. Based on this, a new approach of magnetic solid phase extraction (MSPE) combined with graphite furnace atomic absorption spectrometry (GFAAS) was proposed for the speciation of trace Cr(iii ) and Cr(vi ). Total Cr and Cr(iii ) were adsorbed on Fe3 O4 @SiO2 @IDA under pH 3 and 5, respectively, followed by elution with 1.5 mol L −1 HNO3 . And the concentration of Cr(vi ) was calculated by subtracting Cr(iii ) from the total Cr. Factors affecting MSPE (pH of sample solution, concentration and volume of desorption reagent, desorption time, extraction time, sample volume) were investigated and the optimized conditions were achieved. With an enrichment factor of 100-fold, the detection limits of the proposed method were 9.1 and 12.8 ng L −1 for Cr(iii ) and total Cr with the relative standard deviations (RSDs) of 4.8 and 5.2% ( c = 50 ng L −1, n = 7), respectively. In order to validate the accuracy of the proposed method, a certified reference material of GSBZ50009-88 environmental water was analyzed, and the determined value was in good agreement with the certified value. The proposed MSPE-GFAAS method is simple, fast, selective and sensitive for the speciation of trace Cr without any oxidation or reduction process. It has been applied in the speciation of trace Cr in natural water samples with satisfactory results.